Cambarus (Depressicambarus) clairitae, a new species of crayfish (Decapoda: Cambaridae) from Alabama with a review of the halli Group in the subgenus Depressicambarus - Schuster, Guenter A.; Taylor, Christopher A. (Zootaxa, 2016)
Cambarus (Depressicambarus) clairitae, new species, is an epigean crayfish from two drainages of the Locust Fork system in Blount and Jefferson counties, Alabama. It belongs to the halli Group in the subgenus Depressicambarus. The new species is morphologically most similar to Cambarus (Depressicambarus) englishi. They differ in a several morphological characters. Cambarus englishi has a more strongly recurved central projection, a wider areola, and a more distinct and set off rostral acumen than the new species. It also has light gray to white antennae while the antennae of the new species are brown. In addition to the description of the new species, the halli Group in Alabama is discussed.